The Judge Guillermo B. Guevara Foundation awarding of the Order of Kalantiao and distinguished service to justice awards (Judge Guillermo B. Guevara Foundation, 1990)
First Order of Kalantiao bestowed by President Ferdinand E. Marcos to Judge Guillermo B. Guevara on February 15, 1982 at the Ceremonial Hall of the Malacanang Palace.